Global Vertical Distribution of Water Vapor on Mars: Results From 3.5 Years of ExoMars‐TGO/NOMAD Science Operations. Issue 9 (26th September 2022) - Aoki, S.; Vandaele, A. C.; Daerden, F.; Villanueva, G. L.; Liuzzi, G.; Clancy, R. T.; Lopez‐Valverde, M. A.; Brines, A.; Thomas, I. R.; Trompet, L.; Erwin, J. T.; Neary, L.; et al.
Abstract: We present water vapor vertical distributions on Mars retrieved from 3.5 years of solar occultation measurements by Nadir and Occultation for Mars Discovery onboard the ExoMars Trace Gas Orbiter, which reveal a strong contrast between aphelion and perihelion water climates. In equinox periods, most of water vapor is confined into the low‐middle latitudes. In aphelion periods, water vapor sublimated from the northern polar cap is confined into very low altitudes—water vapor mixing ratios observed at the 0–5 km lower boundary of measurement decrease by an order of magnitude at the approximate altitudes of 15 and 30 km for the latitudes higher than 50°N and 30–50°N, respectively. The vertical confinement of water vapor at northern middle latitudes around aphelion is more pronounced in the morning terminators than evening, perhaps controlled by the diurnal cycle of cloud formation. Water vapor is also observed over the low latitude regions in the aphelion southern hemisphere (0–30°S) mostly below 10–20 km, which suggests north‐south transport of water still occurs. In perihelion periods, water vapor sublimated from the southern polar cap directly reaches high altitudes (>80 km) over high southern latitudes, suggesting more effective transport by the meridional circulation without condensation. We show that heating during perihelion, sporadic global dust storms, and regional dust storms occurring annually around 330° of solar longitude ( L S ) are the main events to supply water vapor to the upper atmosphere above 70 km. Plain Language Summary: This study presents new details on the global distribution of Mars water vapor altitude profile based on the daily observations for 3.5 years. We show a strong contrast between northern and southern summer when water vapor is sublimated from the summer polar ice. We find that sublimated water vapor is confined at low altitudes in the northern summer, whereas it directly reaches the upper atmosphere in the southern summer. During solstice periods, global meridional transport from summer to winter hemisphere drives the water vapor distributions. It is suggested that the transport of water vapor by the global circulation is limited by the formation of ice clouds in the northern summer. In contrast, water vapor is more effectively transported to the winter hemisphere in the southern summer because its vertical extent is less constrained by cloud formation in the warm southern summer atmosphere. We show that southern summer is the primary season for the supply of water vapor to the upper atmosphere, in addition to the period of strong dust storms. We also show that water transport from north to south still occurs below 10–20 km in the northern summer season, however it is much reduced relative to the southern summer season. Key Points: We present global vertical distributions of water vapor in the Mars atmosphere from the observations collected for 3.5 years We confirm a strong contrast between aphelion and perihelion water vapor vertical distributions We reveal that water vapor sublimated from the northern polar cap is confined into very low altitudes during the aphelion periods